2012
DOI: 10.4103/2156-7514.93274
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated Cone-beam Breast Computed Tomography and Diagnostic Mammography: Comparison of Radiation Dose, Patient Comfort, And Qualitative Review of Imaging Findings in BI-RADS 4 and 5 Lesions

Abstract: Objective:This pilot study was undertaken to compare radiation dose, relative visibility/conspicuity of biopsy-proven lesions, and relative patient comfort in diagnostic mammography and dedicated cone-beam breast computed tomography (CBBCT) in Breast Imaging-Reporting and Data System (BI-RADS)® 4 or 5 lesions.Materials and Methods:Thirty-six consecutive patients (37 breasts) with abnormal mammographic and/or ultrasound categorized as BI-RADS® 4 or 5 lesions were evaluated with CBBCT prior to biopsy. Administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…Not only has clinical research involving bCT grown 28,61 but the recent FDA approval of the Koning Breast CT system may further increase the availability of clinical cases. 62 Additionally, our group has demonstrated the ability to morph between models in order to create a much larger number of phantoms with user-defined anatomical characteristics. 25 A second limitation of this segmentation routine is the sensitivity of the algorithm to noise in the bCT data set.…”
Section: Discussionmentioning
confidence: 99%
“…Not only has clinical research involving bCT grown 28,61 but the recent FDA approval of the Koning Breast CT system may further increase the availability of clinical cases. 62 Additionally, our group has demonstrated the ability to morph between models in order to create a much larger number of phantoms with user-defined anatomical characteristics. 25 A second limitation of this segmentation routine is the sensitivity of the algorithm to noise in the bCT data set.…”
Section: Discussionmentioning
confidence: 99%
“…6.9 mGy). 114 In a BCT dose assessment study of the UMASS group, the interquartile range and the range of MGD necessary in a BCT exam were lower than in mammography, in spite of the fact that the median value was higher. 115…”
Section: B1 Dose In Bctmentioning
confidence: 99%
“…91 Another study demonstrated a high correlation between cone-beam CT and mammography in the evaluation of BI-RADs 4 and 5 lesions, with better patient comfort. 92 A pilot study investigated the potential role of conebeam CT in monitoring tumour response. 93 In terms of radiation dose, cone-beam CT had a similar or lower glandular dose than conventional mammography.…”
Section: Cone-beam Computed Tomographymentioning
confidence: 99%
“…93 In terms of radiation dose, cone-beam CT had a similar or lower glandular dose than conventional mammography. [89][90][91][92] The current available evidence is derived largely from small-scale studies: further large population studies are needed to investigate the potential application of conebeam CT in breast imaging.…”
Section: Cone-beam Computed Tomographymentioning
confidence: 99%